Strengthening Moral Education: A CIPP-Based Evaluation of the Adab Development Program in an Islamic Senior High School - Ibnu Muthi (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
Adab (moral conduct) plays a fundamental role in shaping students’ character, integrity, and social responsibility within the framework of Islamic education. This study aims to evaluate the effectiveness of the Adab Education Strengthening Program at Al Azhar Islamic Senior High School 4, Bekasi, using the CIPP (Context, Input, Process, Product) evaluation model. Utilizing a qualitative research design, data were collected through in-depth interviews, direct observations, and document analysis. A total of 12 informants were purposively selected, consisting of the school principal, Adab subject teachers, vice principal, and students from various grade levels. The findings indicate that, in the context dimension, the program aligns well with the school’s mission to nurture morally upright students. In the input dimension, adequate teaching resources and qualified educators were available to support program implementation. The process evaluation showed that while the program is well-executed, it lacks systematic and continuous monitoring to ensure consistency and effectiveness. In the product dimension, students demonstrated improved manners and ethical behavior; however, areas such as teacher training and formative assessment still require development. In conclusion, the program has positively contributed to students' moral and character formation, although continuous teacher development and structured evaluations are essential for long-term sustainability. The study provides valuable insights for improving character education in Islamic schools.